Effectiveness of a multifactorial intervention on preventing development of frailty in pre-frail older people: study protocol for a randomised controlled trial. Issue 2 (9th February 2015) - Fairhall, Nicola; Kurrle, Susan E; Sherrington, Catherine; Lord, Stephen R; Lockwood, Keri; John, Beatrice; Monaghan, Noeline; Howard, Kirsten; Cameron, Ian D
Abstract : Introduction: Frailty is a major concern due to its costly and widespread consequences, yet evidence of effective interventions to delay or reduce frailty is lacking. Our previous study found that a multifactorial intervention was feasible and effective in reducing frailty in older people who were already frail. Identifying and treating people in the pre-frail state may be an effective means to prevent or delay frailty. This study describes a randomised controlled trial that aims to evaluate the effectiveness of a multifactorial intervention on development of frailty in older people who are pre-frail. Methods and analysis: A single centre randomised controlled trial with concealed allocation, assessor blinding and intention-to-treat analysis. Two hundred and thirty people aged above 70 who meet the Cardiovascular Health Study frailty criteria for pre-frailty, reside in the community and are without severe cognitive impairment will be recruited. Participants will be randomised to receive a multifactorial intervention or usual care. The intervention group will receive a 12-month interdisciplinary intervention targeting identified characteristics of frailty and problems identified during geriatric assessment. Participants will be followed for a 12-month period. Primary outcome measures will be degree of frailty measured by the number of Cardiovascular Health Study frailty criteria present, and mobility measured with the Short Physical Performance Battery. Secondary outcomes will include measures of mobility, mood and use of health and community services. Ethics and dissemination: The study was approved by the Northern Sydney Local Health District Health Research Ethics Committee (1207-213M). The findings will be disseminated through scientific and professional conferences, and in peer-reviewed journals. Trial registration number: Australian New Zealand Clinical Trials Registry: ACTRN12613000043730.